Thai art currencies of the contemporary - Teh, David (Cambridge, MA The MIT Press, 2017)
"This book fills a resounding silence: it tells a story, as yet unknown, of great significance to the understanding of non-Western contemporary art in global circulation. Since the 1990s, Thai contemporary art has achieved remarkable international visibility, with a host of Thai artists winning critical acclaim and recognition at leading institutions. For the past 25 years, not a single art historical monograph on the subject has been published, nor even a volume of essays. Not since 1992, when Apinan Poshyananda's Modern Art in Thailand was published, has there been any serious study of Thai art. This book is not only a long overdue update on Thai art since that time, but it is the first book to identify new vectors for its historicisation in cultural and media histories, anthropology, and the growing discourses of exhibition-making and contemporaneity. It affords rare critical purchase on the awkwardly overlapping frames through which Thai contemporary art has been exhibited, understood, and valued"-- Provided by publisher.
Includes bibliographical references (pages 243-261) and index.
Keywords: Art, Thai -- 21st century